2021
DOI: 10.1007/s12094-021-02712-8
|View full text |Cite
|
Sign up to set email alerts
|

Quality indicators and excellence requirements for a multidisciplinary lung cancer tumor board by the Spanish Lung Cancer Group

Abstract: Multidisciplinary care is needed to decide the best therapeutic approach and to provide optimal care to patients with lung cancer (LC). Multidisciplinary teams (MDTs) are optimal strategies for the management of patients with LC and have been associated with better outcomes, such as an increase in quality of life and survival. The Spanish Lung Cancer Group has promoted this review about the current situation of the existing national LC-MDTs, which also offers a set of excellence requirements and quality indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 48 publications
(139 reference statements)
0
10
0
Order By: Relevance
“…25 26 Although UK data demonstrates a correlation between quality of lung cancer services and 1-year survival rates, 27 evidence to determine optimal lung cancer MDT case volumes is lacking, A recent consensus statement from Spain describes quality indicator requirements for a lung cancer MDT but does not make recommendations on case volume. 28 This supports the urgent need to assess and ensure the quality of lung cancer services is adequate across all centres in Australia, to be able to track MDT copyright.…”
Section: Impact From the Covid-19 Pandemicmentioning
confidence: 76%
See 1 more Smart Citation
“…25 26 Although UK data demonstrates a correlation between quality of lung cancer services and 1-year survival rates, 27 evidence to determine optimal lung cancer MDT case volumes is lacking, A recent consensus statement from Spain describes quality indicator requirements for a lung cancer MDT but does not make recommendations on case volume. 28 This supports the urgent need to assess and ensure the quality of lung cancer services is adequate across all centres in Australia, to be able to track MDT copyright.…”
Section: Impact From the Covid-19 Pandemicmentioning
confidence: 76%
“…At the same time, healthcare resource planning should be cognisant of research from other areas of medicine (including lung cancer surgery) demonstrating that high case volume is associated with better outcomes across a wide range of procedures and conditions 25 26. Although UK data demonstrates a correlation between quality of lung cancer services and 1-year survival rates,27 evidence to determine optimal lung cancer MDT case volumes is lacking, A recent consensus statement from Spain describes quality indicator requirements for a lung cancer MDT but does not make recommendations on case volume 28. This supports the urgent need to assess and ensure the quality of lung cancer services is adequate across all centres in Australia, to be able to track MDT delivery and outcomes over time and to support newly established MDTs.…”
Section: Discussionmentioning
confidence: 99%
“…The multidisciplinary team (MDT) meeting or (molecular) tumor board may be appropriate forums for such cases to be discussed in detail. [46][47][48] In summary, the patient should be given the benefit of any doubt, submitting and testing a sample, even down to 5% tumor content. Virtually any "positive" result is a "win".…”
Section: E T E R M I N I N G S a M P L Ementioning
confidence: 99%
“…Thus, the patient could still harbour a targetable mutation that has not been detected. The multidisciplinary team (MDT) meeting or (molecular) tumor board may be appropriate forums for such cases to be discussed in detail 46–48 …”
Section: Recommendations: By Process Stepmentioning
confidence: 99%
“…For example, radical local therapy combined with osimertinib continuation should be considered for patients progressed on osimertinib, when the progression occurs without actionable biomarkers emergence and except those who developed extensive progression: in this setting, sharing the case in a multidisciplinary team is recommended (15). Recently, The Spanish Lung Cancer Group promoted a review focused on quality indicators to the best care of lung cancer patients: the authors concluded that time, resources, leadership, recording of activity and administrative support are the main factors for the success of MDTs (16). In order to ensure the continuity of the cases presentation during the COVID-19 pandemic, the successful experience of transition to virtual thoracic tumor board can be also used to overcome the problem of distance barriers presented in many hospital centers (17).…”
Section: Editorialmentioning
confidence: 99%